Solve this equation using the quadratic formula:

2x(x-4) - 3(x+5) = x(1-x) -16

### 2 Answers | Add Yours

The equation 2x(x-4) - 3(x+5) = x(1-x) -16 has to be solved.

2x(x-4) - 3(x+5) = x(1-x) -16

= 2x^2 - 8x - 3x - 15 = x - x^2 - 16

= 3x^2 - 12x + 1 = 0

`x = (-12 +-sqrt(144 - 12))/6`

= `(-6+-sqrt 33)/3`

**The roots of the equation `2x(x-4) - 3(x+5) = x(1-x) -16` are **`(-6+-sqrt 33)/3`

`2x(x-4)-3(x+5)=x(1-x)-16`

`2x^2-8x-3x-15=x-x^2-16`

`3x^2-12x+1=0`

`x^2-4x+1/3=0`

`x^2-4x+4+1/3=4`

`x^2-4x+4=11/3`

`(x-2)^2=11/3`

`x-2= +-sqrt(11/3)`

`x=2+-sqrt(11/3)`

`x_1=0.085145784487323780049796177260`

`x_2=3.9148542155126762199502038227396`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes